2017
DOI: 10.1111/bjh.14637
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single‐agent bortezomib as post‐transplant consolidation therapy on multiple myeloma‐related bone disease: a randomized phase II study

Abstract: Summary This phase II study explored the effects of bortezomib consolidation versus observation on myeloma‐related bone disease in patients who had a partial response or better after frontline high‐dose therapy and autologous stem cell transplantation. Patients were randomized to receive four 35‐day cycles of bortezomib 1·6 mg/m2 intravenously on days 1, 8, 15 and 22, or an equivalent observation period, and followed up for disease status/survival. The modified intent‐to‐treat population included 104 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
0
14
1
Order By: Relevance
“…The contradictory effects on OS shown in Mellqvist's study might be due to the fact that all patients were bortezomib-naive before consolidation and more patients in the control group received bortezomib-containing intensive therapy after first relapse (48/183 vs. 19/187) 25 . The study by Sezer et al 22 revealed similar effects on OS in the bortezomib arm compared with observation (HR = 1.01). Of note, none of these studies was statistically significant in terms of OS.…”
Section: Bortezomib-based Consolidation Therapymentioning
confidence: 68%
See 2 more Smart Citations
“…The contradictory effects on OS shown in Mellqvist's study might be due to the fact that all patients were bortezomib-naive before consolidation and more patients in the control group received bortezomib-containing intensive therapy after first relapse (48/183 vs. 19/187) 25 . The study by Sezer et al 22 revealed similar effects on OS in the bortezomib arm compared with observation (HR = 1.01). Of note, none of these studies was statistically significant in terms of OS.…”
Section: Bortezomib-based Consolidation Therapymentioning
confidence: 68%
“…Of the ten included RCTs [19][20][21][22][23][24][25][26][27] , there were nine phase III studies and one phase II study included in the analysis. Bortezomib-based regimens were administered as consolidation therapy in seven RCTs [19][20][21][22]25,27 and as maintenance therapy in three RCTs 23,24,26 , following the initial therapy. Only one RCT was conducted in the non-transplantation setting 24 .…”
Section: Characteristics Of Included Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the evaluation of bone markers in the consolidation setting should be performed cautiously. The administration of bone-modifying agents during the induction treatment may have a residual beneficial effect, and thus, significant changes in bone markers may not become evident during the consolidation phase 15 . All our patients had received upfront bortezomib-based regimens with bisphosphonates; thus, several bone markers may have reached their plateau levels.…”
Section: Dear Editormentioning
confidence: 99%
“…Thus, the evaluation of consolidation regimens in terms of efficacy and bone‐related markers is intriguing. Regarding the latter, published data are rather scarce . Therefore, the aim of this prospective study was to assess the efficacy and safety of bortezomib and lenalidomide (VR) combination, without dexamethasone, as consolidation regimen in transplant‐eligible NDMM patients and also determine its effects on bone metabolism and SRE incidence in the absence of bisphosphonates (BPs) coadministration.…”
Section: Introductionmentioning
confidence: 99%